Lethal Disease in Dogs Naturally Infected with Severe Fever with Thrombocytopenia Syndrome Virus - Ishijima, Keita; Tatemoto, Kango; Park, Eunsil; Kimura, Masanobu; Fujita, Osamu; Taira, Masakatsu; Kuroda, Yudai; Mendoza, Milagros Virhuez; Inoue, Yusuke; Harada, Michiko; Matsuu, Aya; Shimoda, Hiroshi; et al. (Viruses, 2022)
Severe fever with the thrombocytopenia syndrome virus (SFTSV) causes fatal disease in humans, cats, and cheetahs. In this study, the information on seven dogs with SFTS was summarized. All dogs showed anorexia, high fever, leukopenia, and thrombocytopenia, two dogs showed vomiting and loose stool, and five dogs had tick parasites. All dogs also had a history of outdoor activity. The SFTSV gene was detected in all dogs. Remarkably, three dogs (43%) died. SFTSV was isolated from six dogs and the complete genomes were determined. A significant increase in anti-SFTSV-IgG antibodies was observed in two dogs after recovery, and anti-SFTSV-IgM antibodies were detected in four dogs in the acute phase. Using an ELISA cut-off value of 0.410 to discriminate between SFTSV-negative and positive dogs, the detection of anti-SFTSV-IgM antibodies was useful for the diagnosis of dogs with acute-phase SFTS. Four out of the ninety-eight SFTSV-negative dogs possessed high anti-SFTSV IgG antibody titers, indicating that some dogs can recover from SFTSV infection. In conclusion, SFTSV is lethal in some dogs, but many dogs recover from SFTSV infection.